EARLY CHILDHOOD HEALTH AND NUTRITION: UNDERSTANDING THE ISSUE OF STUNTING AND HOW TO PREVENT IT - Putri, Rahma Eka; Rahman, Riri Jufita; Juwita, Juwita; Annisa, Rifka; Juanti, Eka; Maswati, Maswati (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The most significant and valuable asset for society as a whole is health, and in order to recognize this state, proper dietary intake is required. Nutrition is a food ingredient that can improve a person's health when consumed. Thus, nutrition and health are closely linked. Early childhood nutrition preparation is a crucial issue that parents should focus on. because a child's early dietary intake will have an impact on their adult growth and development. Children's health and intelligence are directly linked to their nutrition, which cannot be separated. Additionally, children's growth and development will be supported by the nutrition they receive. This study aims to raise parents' and educators' understanding of the significance of a child's appropriate nutritional intake. A literature review of the findings and a discussion of research relevant to the program to be implemented constituting the research methodology. It is anticipated that this research will help parents and teachers at home by raising awareness of the need to monitor children's nutritional intake and sufficiency, which is also one of the key elements promoting growth and development.